LATE ALBIAN-CENOMANIAN PLANKTONIC FORAMINIFERAL BIOSTRATIGRAPHY, TAXONOMY AND PALEOCEANOGRAPHIC INFERENCES - GILARDONI, SILVIA ELENA (Università degli Studi di Milano, 2017)
The mid-Cretaceous period (about 120 Ma to 80 Ma) was characterized by unusually warm climate, low thermal gradient between latitudes and by a series of Oceanic Anoxic Events (OAEs) promoting deposition of black shales (e.g. Bréhéret, 1988; Gale et al., 1996; Coccioni, 2001; Bornemann et al., 2005; Gambacorta et al., 2014, among others). During the late Albian-Cenomanian (~105-93 Ma), a major radiation of planktonic foraminifera did occur for the first time in their evolutionary history and was marked by the appearance of novel morphologies (biserial taxa and single-keeled trochospiral taxa with supplementary apertures) and by the development of new and more complex wall textures (macroperforate, muricate and costellate) on planispiral and trochospiral taxa that lasted until the end of the Cretaceous (González-Donoso et al., 2008; Lipson-Benitah, 2008; Georgescu and Huber, 2006, 2009; Huber and Leckie, 2011). However, the often imprecise usage of the key taxonomic criteria for species identification (morphology vs. wall texture) and/or broad species concept used for the identification of some upper Albian-Cenomanian species have lead to uncertainties in the planktonic foraminiferal biozonation. This study is aimed 1) to review the upper Albian-Cenomanian planktonic foraminiferal species in order to clarify the key taxonomic features of some often misidentified species (e.g., Th. reicheli, R. cushmani, R. montsalvensis); 2) to refine the planktonic foraminiferal biozonation according to the revised taxonomy; 3) to describe the planktonic foraminiferal preferred trophic regime in the upper Albian-Cenomanian interval through the observation and comparison of relative abundances and diversity of species with inferred similar depth ecology; and 4) to clarify the planktonic foraminiferal response to the upper Albian Oceanic Anoxic Event 1d (OAE1d) (Erbacher and Thurow, 1997) and to the Mid Cenomanian Event (MCE) (Ernst et al., 1983). The upper Albian-Cenomanian samples analyzed were selected from different ...